(untitled) (UUM Journal of Legal Studies, 2020)
The advantage of digital era with unlimited access to the Internet is enjoyed by most people globally including the young and children. However, policy-makers concern with the advancement of Internet and propagate the idea of shielding and segregating the children from the harm that may cause from access to the Internet, including breach of online privacy of the children. Children are not sensitive with their online privacy or do not know how to protect their online privacy. Hence, some countries have enacted specific legislation to protect the privacy of the children such as the Children’s Online Privacy Protection Act (COPPA) in the United States of America or introduced self-regulatory initiatives on online child privacy like in the European Union. At the international level, the Convention on the Rights of the Child was introduced in 1989 by the United Nation to protect the children. In Malaysia, the government introduces the Child Act 2001 and the Sexual Offences against Children Act 2017 to protect the children. However, how far these two Acts protect the online privacy of the children in Malaysia? Thus, the article seeks to examine the legal protection of children online informational privacy in Malaysia. The article adopts doctrinal research methodology which is mainly library research approach. The article finds that the current regimes of laws do not adequately protect the online privacy of the children in Malaysia. It is suggested that amendment or enactment of the laws to that effect be made.